DISEASE ACTIVITY INDICES AND C-REACTIVE PROTEIN PREDICT SWITCHING OF THE FIRST BIOLOGICAL AGENT IN ANKYLOSING SPONDYLITIS PATIENTS – A SINGLE-CENTER OBSERVATIONAL STUDY - Marius Trandafir (Romanian Journal of Rheumatology, 2017)
Objective. The study aimed at observing drug survival and determining potential predictors of anti-TNFα switch among ankylosing spondylitis (AS) patients. Methods. The study retrospectively recorded clinical data of patients fulfilling modified New York criteria in a single university clinic. The data were analyzed using appropriate statistical test, which were considered significant if p < 0.05. Results. A total of 120 patients met the inclusion criteria. Switchers had a median BASFI score of 2.7, a median ASDASCRP of 1.59 and a 41.7% prevalence of uveitis, compared to non-switchers which had a median BASFI score of 2.0, a median ASDASCRP of 1.20 and a uveitis prevalence of 22.9% respectively (p = 0.009; p = 0.025; p = 0.043). After a median of 7.0 years of observation, 96 patients (80.0%) were still being treated with their first anti-TNFα agent, with a Kaplan-Meier survival time estimate of 11.5 (10.1-12.9) years. The Kaplan-Meier study of the time of treatment until switch of the first biologic agent according to ASDASCRP categories revealed 9.3 (8.8-9.8) years for inactive disease, 10.6 (8.8-12.5) years for moderately active disease and 7.1 (5.7-8.5) years for highly active disease. The switch hazard ratio for CRP was 1.019 (1.007-1.031; p = 0.002), for BASDAI 1.226 (1.017-1.477; p = 0.032), for BASFI 1.264 (1.057-1.513; p = 0.010) and for ASDASCRP 1.592 (1.173-2.159; p = 0.003). Conclusion. Romanian AS patients on anti-TNFα agents exhibit high retention rate and drug survival of anti-TNFα agents. Switchers have significantly higher baseline disease activity indices which, along baseline acute phase reactants, can significantly predict switching of the first anti-TNFα agent. Patients with AS treated with anti-TNFα agents had a higher prevalence of uveitis than those who did not therapeutic switch.